Stereo Thermal Marking Velocimetry - Savelyev, Ivan; Fuchs, Julian (Frontiers in Mechanical Engineering, 2018)
This paper presents a novel approach to measuring and mapping shape and motion of the water surface. The approach combines and borrows from existing techniques, such as stereo imaging shape recognition and tracking, infrared laser marking and thermography, and particle image velocimetry. The system consists of a high power infrared laser beam controlled by a programmable marking head and two infrared cameras tracking the thermal pattern projected by the beam onto the water surface. The paper provides detailed description of the setup, discusses the choice of the thermal pattern, and describes the infrared image processing algorithm. An example of resolved surface shape and velocity maps is given for an experiment conducted in a laboratory wave tank.